Measurements of inclusive jet spectra in pp and central Pb-Pb collisions at √SNN=5.02 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Klewin, Sebastian; Knichel, Michael Linus; Köhler, Markus Konrad; Leardini, Lucia; et al. (Physical review, 2020)
This article reports measurements of the p(T)-differential inclusive jet cross section in pp collisions at root S = 5.02 TeV and the p(T)-differential inclusive jet yield in Pb-Pb 0-10% central collisions at root S-NN = 5.02 TeV. Jets were reconstructed at midrapidity with the ALICE tracking detectors and electromagnetic calorimeter using the anti-k(T) algorithm. For pp collisions, we report jet cross sections for jet resolution parameters R = 0.1-0.6 over the range 20 < p(T,jet) < 140 GeV/c, as well as the jet cross-section ratios of different R and comparisons to two next-to-leading-order (NLO)-based theoretical predictions. For Pb-Pb collisions, we report the R = 0.2 and R = 0.4 jet spectra for 40 < p(T,jet) < 140 GeV/c and 60 < p(T,jet) < 140 GeV/c, respectively. The scaled ratio of jet yields observed in Pb-Pb to pp collisions, R-AA, is constructed, and exhibits strong jet quenching and a clear p(T) dependence for R = 0.2. No significant R dependence of the jet R-AA is observed within the uncertainties of the measurement. These results are compared to several theoretical predictions.
ALICE Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M.C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim. M. Kim, S. Klewin, M.L. Knichel, M.K. Köhler, L. Leardini, N.A. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, J. Stachel, D.F. Weiser, B. Windelband, A. Yuncu und 978 weitere
SNN steht im Titel unter dem Wurzelzeichen, NN ist tiefgestellt
Gesehen am 16.04.2020